Tantangan dan tren: Perkembangan bank syariah di era pasca pandemi - Muqaffa, Dzaki (Maliki Interdisciplinary Journal, 2024)
The development of Islamic banks in the post-pandemic era is influenced by changes in consumer patterns, financial technology innovation, and economic regulations and policies. Islamic banks must accelerate digital transformation, develop products that comply with sharia values, and improve Islamic financial literacy. Cooperation between the government, regulators, Islamic financial institutions, and educational institutions is important to support the growth of the Islamic banking sector. In facing post-pandemic challenges and opportunities, Islamic banks need to continue to adapt to market changes, utilize technology, and empower Islamic financial literacy to strengthen their position in the Islamic banking sector.